Alunogen from the sulfate efflorescence of the Stone Town Nature Reserve in Ciężkowice (the Outer Carpathian Mountains, Poland) - Marszałek, Mariola; Gaweł, Adam (Geology, Geophysics and Environment, 2023)
Alunogen (Al2(SO4)3∙17H2O), a rare secondary mineral, has been found in the efflorescence on sandstones from the Stone Town Nature Reserve in Ciężkowice, southeastern Poland. This is probably the first find of this salt on such rocks in Poland. Alunogen forms in various geological environments, but mainly from the oxidation of pyrite and other metal sulfides in ore deposits and Al-rich Earth materials under low-pH conditions. Its crystallization at this particular site depends on a set of necessary physicochemical (pH, concentration), climatic (season, temperature, humidity), site-related (location and protection of efflorescence), and mineralogical (the presence of pyrite) conditions. This paper presents the mineralogical and geochemical characteristics of the alunogen from the Stone Town Nature Reserve (based on SEM-EDS, XRPD, EPMA and Raman spectroscopy methods) as well as of the efflorescence itself (based on XRPD and STA coupled with QMS and FTIR for the analysis of gas products). Crystals of alunogen take the shape of flakes, often with a hexagonal outline, clustered in aggregates forming a cellular network. Its calculated formula is (Al1.96Fe3+0.01)Σ1.97(SO4)3∙17H2O (based on 12 O and 17 H2O). The unit-cell parameters refined for the triclinic space group P1 are: a = 7.423 (1) Å, b = 26.913 (5) Å, c = 6.056 (1) Å, a = 89.974 (23)°, b = 97.560 (25)°, g = 91.910 (22)°. The Raman spectra (SO4) bands are: intensive 995 cm−1 (ν1); low-intensive 1069, 1093 and 1127 cm−1 (ν3); low-intensive 419 and 443; medium-intensive 470 cm−1 (ν2); and medium-intensive 616 cm−1 (ν4). Those at 530, 312 and at 338 cm−1 are assigned to water vibrations and those at 135, 156, 180 cm−1 to the lattice modes. Although the efflorescence contained an admixture of other minerals (pickeringite, gypsum and quartz), the predominant alunogen is almost chemically pure and the above parameters are consistent with the values reported in the literature for alunogen from different locations and of various origins.